PENGARUH RASIO PROFITABILITAS DAN RASIO SOLVABILITAS TERHADAP KINERJA KEUANGAN PADA PERBANKAN YANG TERDAFAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Maria Novita Setia; Yuli Ermawati (Jurnal Ekonomi, Bisnis dan Social, 2024)
This study aims to determine the effect of Profitability Ratios proxied by Net Interest Margin (NIM) and Operating Expenses Operating Income (BOPO) and Solvability Ratios proxied by Capital Adequacy Ratio (CAR) and Debt To Equity Ratio (DER) on Financial Performance proxied by Return On Assets (ROA) in Banking Those Registered on the Indonesia Stock Exchange for the 2019-2021 period. The data used in this study were obtained from financial reports and annual banking reports registered on the IDX through the website www.idx.id. The sample for this study amounted to 15 out of 43 populations using the purposive sampling method. The analysis technique used is multiple regression analysis. The results of the f test show that the profitability variable is proxied by NIM and BOPO and Solvency is proxied by CAR and DER together has an influence on financial performance (ROA). The results of the t test show that the variable profitability (NIM) has no effect on financial performance (ROA) and profitability (BOPO) has an effect on financial performance (ROA) and solvability variable (CAR) has an effect on financial performance (ROA) and solvency (DER) has an effect on financial performance (ROA).